Water and sediment quality of an agro-industrial area through different approaches: Physicochemical parameters and ecotoxicity with amphibians - Peluso, Julieta (2023)
Amphibians are subject to several stressors in the aquatic and terrestrial environments, and human activities have profoundly impacted this vertebrate group. The aim of the present study was to analyze physicochemical parameters, metals and pesticide residues, and the toxicity of water and sediment samples from an environment with high agricultural activity (S1: Salto stream; S2: drainage channel downstream from S1) by means of bioassays using Rhinella arenarum (Amphibia: Anura) larvae. Metals and pesticides were analyzed in water and sediment samples by fluorescence spectrometer of X-ray by total reflection and ultra-high-performance liquid chromatography-MS/MS, respectively. For lethality bioassays, 10 larvae (in triplicate) were exposed for 504 h to water and sediment samples. Also, 50 larvae were exposed for 96 h (in triplicate) to water and sediment samples for the evaluation of biomarkers of neurotoxicity, oxidative stress, and genotoxicity. Twenty-six different pesticides (mainly herbicides) were detected in both sites, and Cu, Zn, and Pb exceeded the limit for protection of aquatic life. Lethality was observed in larvae exposed to water and sediment samples from both sites at chronic exposure. Oxidative stress was observed in larvae exposed to both sites. In larvae exposed to samples from S1, alterations in the neurotoxicity biomarkers were observed. These results alert about the degradation of the sites and highlight the need to monitor and control the use of pesticides.